Impact of Conductor Slots on Inductance and Efficiency of a Machine - Awah, C. C.; Diyoke, G. C.; Amaghionyeodiwe, C. A.; Obasi, O.; Nnabuenyi, I. K.; Oti, S. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The number of conductor slot and its winding arrangement would always affect the performance of electric machines; this would include effect on its efficiency and inductance profiles, which is indispensable in the accurate prediction of machine’s output values. Similarly, stator and rotor pole selections of PM machines are critical in determining the machine’s output performances. Impact of conductor slot number on machine’s performance indices such as: cogging torque, flux, inductances and torque ripple of a double stator (DS) machine is researched and presented in this study. The study provides a guide to machine designers and operators on the electromagnetic implications of doubling or halving the slot number of a given electric machine. The compared machine types have six (6) and twelve (12) conductor slots; however, with a fixed pole number of fourteen (14), designated as DS 6-14 and DS 12-14, for the six (6)-slot and twelve (12)-slot machine types respectively. ANSYS/MAXWELL-2D software simulation package is utilized in the entire analyses and it is implemented through finite element analysis method. Predicted torque per magnet volume of the DS 6-14 and DS 12-14 machine types at a copper loss of 30 W is 226.56 kNm/m3 and 291.62 kNm/m3 respectively. This implies that it would be more economically viable to manufacture the DS 12-14 machine type than its 6-stator slot counterpart, considering its output torque per magnet volume. It is also revealed that the DS 6-14 configuration has larger inductances and higher quadrature (Q)-axis flux compared to its counterpart, albeit; with higher number of undesirable features such as high cogging torque and torque ripple amplitudes. However, the DS 12-14 machine type exhibits greater value of direct (D) axis flux compared to its equivalent 6-slot machine, in addition to other advantages.